Synergistic recycling of calcined clayey sediments and water potabilization sludge as geopolymer precursors: Upscaling from binders to precast paving cement-free bricks. (15th February 2017) - Messina, F.; Ferone, C.; Molino, A.; Roviello, G.; Colangelo, F.; Molino, B.; Cioffi, R.
Highlights: Calcined sediments and potabilization sludge were used as geopolymer precursors. Precast geopolymer paving bricks were produced after upscaling process. Significant results were obtained for sustainable production of building materials. The proposed recycling route is very advantageous for reservoir management. Abstract: The building materials industry is facing relevant challenges in terms of sustainability requirements. The same challenge is expected for other anthropogenic activities such as reservoir management. In this study, in the light of industrial ecology approach, two wastes, namely clayey sediments and water potabilization sludge, generated through reservoir life cycle, were used in a synergistic way in the synthesis of sustainable geopolymer binders. In order to guarantee a productive equilibrium between the different yearly evolution of building materials demand and wastes production by the basin, precast materials have been regarded as optimum potential application. In this regard, calcination conditions, mix design and curing conditions were preliminarily optimized. Particularly, geopolymerization kinetics were evaluated by means of mechanical and microstructural characterization of pastes to assess the influence of early age curing conditions and mix design on the engineering performance and, afterwards, the product was upscaled to a typical precast concrete element. The whole set of results demonstrated the feasibility of the proposed recycling route, revealing highly promising perspectives for further studies and broader application field.